Pretreatment of NaCl enhances the drought resistance of cotton by regulating the biosynthesis of carotenoids and abscisic acid - Ni, Kesong; Dai, Maohua; Lu, Xuke; Zhang, Yuexin; Fan, Yapeng; Xu, Nan; Feng, Xixian; Huang, Hui; Wang, Jing; Rui, Cun; Zhang, Hong; Lei, Yuqian; et al. (Frontiers in Environmental Science, 2022)
Drought stress is one of the abiotic stresses that limits crop production and greatly affects crop yield. Enhancement of plant stress resistance by NaCl pretreatment has been reported, but the mechanism by which NaCl pretreatment activates cotton stress resistance remains unclear. In this study, Gossypium hirsutum cv H177 was used to design three mock treatments (ddH2O) – 15% PEG6000 (polyethylene glycol) for 72 h, 50 mM NaCl for 6 h and 15% PEG6000 (polyethylene glycol) for 72 h – to explore the molecular mechanism by which NaCl improves the drought tolerance of cotton. The results showed that pretreatment with 50 mM NaCl could alleviate the adverse effects of PEG on cotton seeds. We found that NaCl enhanced the drought resistance of cotton by regulating genes related to the carotenoid and ABA downstream synthesis pathways. This study provides a new reference for the study of drought resistance in cotton and a theoretical basis for the molecular breeding of cotton. Keywords: NaCl pretreatment, carotenoid metabolism, cotton, drought resistance, abscisic acid.